2022
DOI: 10.1101/2022.04.23.22273766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical performance of 17 commercially available point-of-care tests for CRP to support patient management at lower levels of the health system

Abstract: Accurate and precise point-of-care (POC) testing for C-reactive protein (CRP) can help support healthcare providers in the clinical management of patients. Here, we compared the analytical performance of 17 commercially available POC CRP tests to enable more decentralized use of the tool. The following CRP tests were evaluated. Eight quantitative tests: QuikRead go (Aidian), INCLIX (Sugentech), Spinit (Biosurfit), LS4000 (Lansionbio), GS 1200 (Gensure Biotech), Standard F200 (SD Biosensor), Epithod 616 (DxGen)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rapid point-of-care C-reactive protein (CRP) tests could be particularly well suited for this indication, because they are inexpensive ($2 USD/test), generate results in 3 minutes, and can be performed with a fingerstick specimen. 15 Multiple studies have reported that CRP has superior diagnostic characteristics for the detection of TB at the time of HIV diagnosis, compared with the W4SS alone. [16][17][18][19] The WHO conditionally recommends the use of CRP with a cut-off of 5mg/L to screen for active TB in PLWH, with the caveat that more data are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid point-of-care C-reactive protein (CRP) tests could be particularly well suited for this indication, because they are inexpensive ($2 USD/test), generate results in 3 minutes, and can be performed with a fingerstick specimen. 15 Multiple studies have reported that CRP has superior diagnostic characteristics for the detection of TB at the time of HIV diagnosis, compared with the W4SS alone. [16][17][18][19] The WHO conditionally recommends the use of CRP with a cut-off of 5mg/L to screen for active TB in PLWH, with the caveat that more data are needed.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is available as a simple, rapid, low-cost (<$US 2), point-of-care test, which is available from a variety of manufacturers. 15 Further study is necessary to define optimal CRP thresholds, which may potentially vary by number and type of symptoms. Moreover, CRP would not replace diagnostic testing for TB or other opportunistic infections and non-communicable diseases.…”
mentioning
confidence: 99%